Application of Nano-Biosensors Combined with Microbiological Tests for Early Detection of Microbial Contaminants in Blood - Shukur, Wameedh Sabah; Kareem, Ameer Awad Aziz; Mohammed, Mustafa Basim; Dawood, Ayat Hamza Shahit (American Journal of Biology and Natural Sciences, 2025)
Motivated by the characteristics of microbial contamination in blood, the prospects of nano-biosensors in terms of microbial detection are presented. Principles, modes, and recent advances of various aspects of nanosensors with microbiological tests are reviewed. A combination of microbiological testing and nano-biosensors can facilitate early detection of microbial contamination and reveal vital indicators of contamination. Microbes grow in blood and produce diverse hazardous byproducts, resulting in skin issue, allergies, organ failure and ultimately death. Although microbial contaminant types, sources, or formation mechanisms have been recognized and suitable preventive/suppressive steps are implemented, early identification remains a critical priority. Similarly, blood quality deterioration emerges as a result of metabolic products of microbial contaminants. Different analytical or microbial tests are widely applied for microbial examination in blood. Nonetheless, the synergy between nano-biosensors and these techniques can ensure rapid and highly sensitive detection of microbial contaminants.